OPTIMALISASI SISTEM INFORMASI BERBASIS AGILE UNTUK PENGELOLAAN BIAYA VARIABEL DAN EXCHANGE RATE DI INDUSTRI FMCG - Saputra, Muhammad Rizky; Voutama, Apriade (Jurnal Sistem Informasi (JUSIN), 2025)
In the Fast Moving Consumer Goods (FMCG) industry, managing variable costs and exchange rates is a major challenge that affects operational efficiency and business decision-making. This study aims to develop an Agile-based information system that enables real-time data integration to improve transparency and accuracy in recording variable costs and exchange rates. The system was developed using the Agile Software Development methodology, consisting of Product Backlog, Sprint Planning, Daily Scrum, Development, Testing, and User Acceptance Testing (UAT). Key features include a variable cost and exchange rate dashboard, which provides structured data presentation, and an input form that facilitates users in entering and managing data according to operational needs. Testing was conducted through UAT involving the System Developer, IT Product team, and production team users. The results indicate that the system enhances cost recording efficiency, provides better visibility of exchange rate fluctuations, and accelerates data validation processes.